Acceptance of Smartphone Technology as Mobile Learning Tool Among Colleges of Education Students in Nigeria - Gambari, A. I.,; Abubakar, M. A; Yahaya, A.; Adamu, B. (Kashere Journal of Education, 2021)
This study investigates “Acceptance of Smartphone Technology as Mobile Learning Tool among Colleges of education Students in Nigeria”. Descriptive survey research design was used for the study. A sample size of 376 was selected from the population using simple random sampling techniques. The instrument used for data collection was questionnaires which consist of twenty questions. It was validated by three experts; pilot tested at college of education Azare and subjected to reliability test using split half method. A reliability coefficient of 0.75 was obtained using Cronbach Alpha. Data collected was analyzed using statistical package for social sciences (SPSS). Mean and standard deviation were used to answer the research questions accordingly. The findings revels that, College students utilized their smartphones as mobile learning tool. They mostly do assignments, search relevant educational materials, send and receive educational mails from teachers and experts using their smartphones. Similarly, college students also find it very simple and easier to operate smartphone as mobile learning tool. It was recommended that government should provide reliable and affordable internet connection in the school premises and also control the price of data from private telecommunication companies. Schools should block all pornographic sites to prevent students from accessing these sites. Teachers should be train and encourage to put-in-place what they have learned on the use of smartphone in teaching and learning process.